Development and evaluation of the low back pain questionnaire for personnel working on islands - Yongbin Feng; Wenyu Tang; Yajun Cheng; Xiaoyi Zhou; Xianzhao Wei (Frontiers in Public Health)
BackgroundLow back pain (LBP) is a significant musculoskeletal disorder with multifactorial causes, affecting workforce productivity globally. Personnel working on islands face heightened LBP risk due to intensive training (e.g., heavy lifting, prolonged standing) and harsh environmental conditions (high temperature, humidity, solar radiation). Existing LBP questionnaires, such as the Roland-Morris Disability Questionnaire and Oswestry Disability Index, lack specificity for island personnel's unique challenges. This study aimed to develop and validate the Low Back Pain Questionnaire (LBPQ) tailored to this population, aligning with the biopsychosocial medical model.MethodsThe LBPQ development followed a six-step process: conceptual definition, item generation, purification, dimension extraction, and reliability/validity testing. Through literature review, expert discussions, and interviews with 30 personnel working on islands, a 50-item initial scale was refined to 25 items across five dimensions: Pain Severity, Training, Daily Life, Psychological Impact, and Island Specificity. The final scale was administered to 600 personnel working on islands (experimental group) and 600 personnel working on land (control group). Reliability was assessed via Cronbach's α, while validity included factor analysis, convergent/discriminant validity tests, and correlation with the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI).ResultsThe LBPQ demonstrated excellent reliability for personnel working on islands (Cronbach's α = 0.978) and good validity, with a KMO value of 0.967 and a cumulative variance contribution rate of 93.322%. Confirmatory factor analysis showed optimal model fit (χ2/df = 1.354, CFI = 0.997, RMSEA = 0.024). Convergent and discriminant validity were superior in the island group compared to the control group. Strong correlations were observed with VAS (r = 0.675) and ODI (r = 0.824), confirming alignment with established scales.ConclusionThe LBPQ is a reliable and valid tool for assessing LBP in personnel working on islands, addressing their unique environmental and occupational risks. It enhances clinical understanding of LBP severity and psychosocial impacts, enabling targeted prevention and intervention strategies. Future research should validate its applicability across diverse island environments and further refine its brevity.